Sharp-edged nanoflakes array of CuO with enhanced optical and charge transport properties for Bias-Free tandem solar Water-splitting - Hwang, Sung Won; Han, Gill Sang; Cho, Ju Young; Lee, Dong Un; Han, Hyun Soo; Cho, In Sun (Applied Surface Science, 2022)
Cupric oxide (CuO) is an attractive photocathode material for tandem-type photoelectrochemical water-splitting because it has a small bandgap (1.2 – 1.5 eV), high absorption coefficient, suitable band-edge position, and favorable characteristics such as earth-abundancy, low cost, and non-toxicity. Here, we report a sharp-edged nanoflakes array (SNA) of CuO that dramatically reduces a light reflection loss (<0.4%) in the visible-to-near infrared region. Importanly, the CuO SNA exhibits enhanced charge transport and transfer properties compared with its porous and compact nanoparticle-film counterparts. The resultant CuO SNA generates a much higher photocurrent density above 2.1 mA/cm2 at 0.1 V versus the reversible hydrogen electrode (RHE) under simulated sunlight irradiation (AM1.5G, 100 mW/cm2). Furthermore, we found that post-annealing of the CuO SNA in an oxygen-rich environment increases the photocurrent density to ∼ 6.3 mA/cm2 at 0.0 V vs. RHE, which is the highest performance achieved among all the reported work on CuO photocathodes. Finally, the practical viability of the photocathode was shown by constructing a tandem PEC cell with a photoanode made of titanium oxide (TiO2) branched-nanorods array and demonstrating bias-free solar water-splitting (a solar-to-hydrogen efficiency: ∼ 1.0 %).
Keywords: Bias-free tandem solar water-splitting; Charge transport properties; Cupric oxide; Nano-flakes; Optical transport properties; Photocurrent density; Photoelectrochemical water splitting; Reversible hydrogen electrodes; Sharp-edged nanoflake array; Solar water splitting; Bias-free tandem solar water-splitting; Charge transport; CuO; Light absorption; Sharp-edged nanoflakes array